2004
DOI: 10.1002/ajh.10442
|View full text |Cite
|
Sign up to set email alerts
|

B‐CAM/LU expression and the role of B‐CAM/LU activation in binding of low‐ and high‐density red cells to laminin in sickle cell disease

Abstract: Red blood cells from patients with sickle cell disease (SS RBC) adhere to laminin and over-express the high-affinity laminin receptor basal cell adhesion molecule/Lutheran protein (B-CAM/LU). This receptor has recently been shown to undergo activation in vitro through a protein kinase A-dependent mechanism. Low-density SS RBC express twothirds more B-CAM/LU than high-density SS RBC. However, high-density SS RBC have been identified as most adherent to laminin under flow conditions. We investigated the ability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
33
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…The low-density sickle erythrocytes, containing young erythrocytes, were found to be more susceptible to epinephrine stimulation, whereas the old, highly dense erythrocytes, that contain fewer Lu/BCAM molecules, were found to be most adherent to laminin-a5. 5 Here we report a novel mechanism that drives Lu/BCAM activation on aging erythrocytes, which can account for abnormal erythrocyte adhesion in SCD and other pathological states such as sepsis. We identified a domain within Lu/BCAM that bears homology to the SIGLEC family of sialic acid-binding receptors.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…The low-density sickle erythrocytes, containing young erythrocytes, were found to be more susceptible to epinephrine stimulation, whereas the old, highly dense erythrocytes, that contain fewer Lu/BCAM molecules, were found to be most adherent to laminin-a5. 5 Here we report a novel mechanism that drives Lu/BCAM activation on aging erythrocytes, which can account for abnormal erythrocyte adhesion in SCD and other pathological states such as sepsis. We identified a domain within Lu/BCAM that bears homology to the SIGLEC family of sialic acid-binding receptors.…”
Section: Introductionmentioning
confidence: 92%
“…3 Erythrocytes express 500 to 4000 Lu/BCAM molecules on their surface, a quantity that gradually decreases as erythrocytes shed membrane and become increasingly dense during their lifespan. 4,5 Lu/BCAM can interact with the extracellular matrix (ECM) component laminin-a5, allowing the capturing of erythrocytes through this interaction even under flow conditions. 6,7 As the ECM is normally not exposed to circulating erythrocytes, the function of Lu/BCAM on terminally differentiated erythrocytes is currently unclear.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 Zen et al confirmed that BCAM/Lu is the most important receptor mediating HbS erythrocyte adhesion to laminin under flow and static conditions. 13 The BCAM/Lu interaction with immobilized laminin under flow conditions appeared to be upregulated by protein kinase A (PKA), downstream of β2 adrenergic receptors. 13,14 While BCAM/Lu is found on both reticulocytes and mature erythrocytes, CD36 and VLA-4 expression, however, is limited to reticulocytes.…”
Section: 9mentioning
confidence: 99%
“…13 The BCAM/Lu interaction with immobilized laminin under flow conditions appeared to be upregulated by protein kinase A (PKA), downstream of β2 adrenergic receptors. 13,14 While BCAM/Lu is found on both reticulocytes and mature erythrocytes, CD36 and VLA-4 expression, however, is limited to reticulocytes. CD36 and VLA-4 are among the most extensively studied adhesion receptors.…”
Section: 9mentioning
confidence: 99%
“…In common with the K-Cl system, when K + leaves the cell it is followed by efflux of water, cellular dehydration and increased internal concentration of Hb S. Endothelin (a vasoactive compound that is elevated in SCA patients), prostaglandin E2 and other cytochemokines alter Gardos channel kinetics, provoking dehydration and polymerization of Hb S. 41,42 Sickled can also significantly increase endothelial adhesion. 5,40,43 Everything points to endothelial cell inflammation and activation playing a central role in the vasoocclusion observed in SCD. Monocyte activation, with secretion of proinflammatory cytokines (IL-1 and TNF-α), leads the leukocytes, which are always present in large numbers, to adhere to the inflamed endothelium and interact with the sickled red blood cells.…”
Section: Pathophysiologymentioning
confidence: 99%